The Effect of Feeding Odot Grass and Ecoenzyme Fermented Rice Straw on The Performance of Local Rams - Rohim, R.; G. A. W. Siregar; Yunilas; Muheri (Jurnal Peternakan Integratif, 2023)
This study aims to determine the effect of odot grass and rice straw fermented using ecoenzyme (Garbage Enzyme) on the performance of local male sheep. This research was carried out in the firuza enclosure from September 8 to November 8, 2020. The method used is a complete randomized design (RAL) with 5 practices and 4 repeats. The treatment consists of 100% odot grass + 0% fermented rice straw (PO), 75% odot grass + 25% fermented rice straw (P1), 50% odot grass + 50% fermented rice straw (P2), 25% odot grass + 75% fermented rice straw (P3), 0% odot grass + 100% fermented rice straw (P4). The parameters studied were weight gain, feed consumption, feed conversion and Income Over Feed Cost (IOFC). The results of the study had a significant effect (P<0.01) on weight gain, feed consumption and feed conversion. Based on this study, it can be concluded that high feed consumption is not comparable to low weight gain resulting in high conversion.